Hubungan Pengetahuan dan Sikap Terhadap Tindakan Konsumsi Makanan Cepat Saji ( Fast Food ) pada Siswa Kelas XI SMA Negeri 10 Bandar Lampung - Andalisa, Novia Tri; Adyas, Atikah; Kustiani, Ai (Journal of Education Technology Information Social Sciences and Health, 2025)
Based on the World Health Organization in 2020, it is known that 80% of teenagers in the world often consume fast food, while Indonesian people who consume fast food are around 69%. This study aims to determine the relationship between knowledge and attitudes towards fast food consumption in adolescents. The subjects in this study were all grade XI students at SMA Negeri 10 Bandar Lampung. The number of samples was 164 students taken using the Proportional Random Sampling technique. This type of quantitative research with a cross-sectional design. Data collection used the FFQ form and questionnaire sheet. The results showed that there was a significant relationship between knowledge and fast food consumption with a p value of 0.003 p (≤ 0.05). There was a significant relationship between attitudes and fast food consumption with a p value of 0.030 p (≤ 0.05) at SMA Negeri 10 Bandar Lampung. Thus, it can be concluded that there is a relationship between knowledge and attitudes with fast food consumption in students of SMA Negeri 10 Bandar Lampung. The suggestion is to increase knowledge about nutrition related to fast food so that we can better recognize healthy and safe food to consume.